Perkembangan Perkawinan Adat pada Perkumpulan Marga Nasution di Kabupaten Rokan Hulu Riau - Musdalipah Musdalipah; Zulherman Idris; Desi Apriani; Bujang Rapani; Heni Susanti (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract: Along with the times, now the indigenous Mandailing people can be found in various regions throughout Indonesia. One of the areas where the Mandailing indigenous people can be found is in the Rokan Hulu Regency of Riau. The Mandailing indigenous people in the area live by customary values ??brought from their place of origin, including in the field of marriage. The author is interested in researching how traditional marriages are carried out in the Mandailing community, especially nasution in the current era of globalization. This research was conducted using empirical methods, using primary data, and inductively concluded. The results of the study show that in the development of people's lives, especially in the current era of globalization, some members of the community do not practice it due to economic factors that make it difficult to make honest money payments to women, there are changes in people's thinking that are influenced by modernization or also influenced by foreign cultures. Keywords: Traditional marriage; Development Marga nasution Abstrak: Seiring dengan perkembangan zaman, sekarang masyarakat adat Mandailing dapat ditemui di berbagai daerah di seluruh Indonesia. Salah satu daerah dimana dapat ditemui masyarakat adat Mandailing adalah di daerah Kabupaten Rokan Hulu Riau. Masyarakat adat mandailing di daerah tersebut hidup dengan nilai-nilai adat yang dibawa dari daerah asal, termasuk di bidang perkawinan. Penulis tertarik meneliti bagaimana pelaksanaan perkawinan adat di lingkungan masyarkat Mandailing khususnya nasution di era globalisasi saat ini. Penelitian ini dilakukan dnegan metode empiris, menggunakan data primer dan menyimpulkan secara induktif. Hasil penelitian memperlihatkan bahwasanya dalam perkembangan kehidupan masyarakat, terutama di era globalisisasi saat ini, sebahagian anggota masyarakat tidak menjalankannya dikarenakan faktor ekonomi yang sulit untuk melakukan pembayaran uang jujur kepada pihak perempuan, adanya perubahan pemikiran masyarakat yang dipengaruhi oleh modernisasi atau dipengaruhi juga oleh budaya asing. Kata Kunci: Perkawinan Adat; Perkembangan; Marga nasution